2013
DOI: 10.1021/cm400765b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Anisotropic Concave Gold Nanocuboids with Distinctive Plasmonic Properties

Abstract: Gold nanoparticles have attracted considerable attention owing to their appealing plasmonic properties that have found applications in sensing, imaging, and energy harvesting. In the present article, we report the synthesis of anisotropic concave Au nanocuboids using a seeded growth method controlled by a seed concentration. Unlike conventional nonconcave counterparts which typically present two fundamental plasmonic modes (transverse and longitudinal modes), our experimental measurements and theoretical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 45 publications
2
77
1
Order By: Relevance
“…42 7.5 mL of a growth solution containing a mixture of 2.5 Â 10 À4 M HAuCl 4 and 0.01 M CTAB solutions were added to ve 20 mL conical asks. 42 7.5 mL of a growth solution containing a mixture of 2.5 Â 10 À4 M HAuCl 4 and 0.01 M CTAB solutions were added to ve 20 mL conical asks.…”
Section: Preparation Of Concave Au Nanocuboidsmentioning
confidence: 99%
See 3 more Smart Citations
“…42 7.5 mL of a growth solution containing a mixture of 2.5 Â 10 À4 M HAuCl 4 and 0.01 M CTAB solutions were added to ve 20 mL conical asks. 42 7.5 mL of a growth solution containing a mixture of 2.5 Â 10 À4 M HAuCl 4 and 0.01 M CTAB solutions were added to ve 20 mL conical asks.…”
Section: Preparation Of Concave Au Nanocuboidsmentioning
confidence: 99%
“…48 As the concentration of the AuNR seeds plays an essential role in the control of nanoparticle growth, we have optimized various seed concentrations ranging from 5 Â C 0 to 0.2 Â C 0 (C 0 represents the concentration of the AuNR seed stock solution) to obtain concave nanoparticles, and the resultant products are designated as AuNP-5C 0 , AuNP-2C 0 , AuNP-C 0 , AuNP-0.5C 0 , and AuNP-0.2C 0 . 42 When the seed concentration is reduced to 2 Â C 0 , the grown AuNPs begin to exhibit facets with irregular trapezoidal and triangular structures on the surface. [49][50][51] Such higher seed concentrations normally lead to the isotropic overgrowth of Au seeds, resulting in the formation of a rod-like nanostructure with at surfaces.…”
Section: Morphological Characterization Of the Cauncsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the transverse plasmon mode of DBLNRs split into two peaks, which is a spectral signature of NRs with surface indentations. 63 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12…”
Section: Resultsmentioning
confidence: 99%